Training effects of two different unstable shoe constructions on postural control in static and dynamic testing situations - Turbanski, Stephan; Lohrer, Heinz; Nauck, Tanja; Schmidtbleicher, Dietmar (Physical therapy in sport, 2011)
The aim of this study was to compare training effects on postural control using two different unstable shoe constructions. Twenty-nine healthy subjects participated in this study and were randomly divided into three groups. Two experimental groups (10 subjects in each group) were assigned to a 6 week training program of specific sensorimotor exercises with unstable shoe constructions, one group using MBT ® shoes and one group wearing Reflex Control ® shoes (RC). Subjects in the control group (9 subjects) did not perform balance training. Postural control was measured in one-leg stance in two testing conditions. We recorded postural sway on a force plate (static testing situation) and displacements of a moveable platform (dynamic testing situation) before and after the training period. There were no effects of training with unstable shoe constructions on postural sway in the static testing condition (for comparison of groups: p = 0.990 and p = 0.119). However, the RC group showed statistically significant improvements in the dynamic testing situation ( p = 0.014 compared to control subjects). In the MBT group improvements were not significantly different in comparison to control group ( p = 0.518). Our results indicate that exercises using unstable shoe constructions, particularly the RC, improve postural control only in dynamic conditions.